Teacher's Emotional Support and Math Performance: The Chain Mediating Effect of Academic Self-Efficacy and Math Behavioral Engagement - Yang, Yanfei; Li, Guangzheng; Su, Zhanguo; Yuan, Yuan (Frontiers in Psychology, 2021)
Positive teacher-student interaction can exert a positive influence on student engagement and math performance. As an important part of teacher-student interaction, teachers’ emotional support play an indispensable role in the math performance of junior middle school and elementary school students. This study aims to explores the effects of perceived teachers’ emotional support on math performance, and examines the mediating role of academic self-efficacy and mathematical behavioral engagement. A total of 1,294 students in grades 3-5 and 7-8 from 14 junior middle and primary schools in China took part in the web-based survey. Results showed that: (1)academic self-efficacy mediated the relationship between perceived teachers’ emotional support and math performance of Chinese primary and middle school boys and girls; math behavioral engagement mediated the relationship between perceived teachers’ emotional support and math performance of Chinese primary and middle school boys and girls; (2) The relationship between perceived teachers’ emotional support and math performance of Chinese junior middle school boys and girls was mediated by the chain of academic self-efficacy and math behavioral engagement.